Designing the Revisit Intention of the Tourism Model on Visiting the Borobudur Temple - Rahayu, Sri; Kenamon, Mardiah; Nazipawati, Nazipawati; Yulitiawati, Yulitiawati; Dona, Eka Meiliya (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The purpose of this study was to determine and analyze how the perception of the destination and the visitor experience affected tourists' satisfaction when they visited Central Java Province (Borobudur Temple); how these factors also affected tourists' intention to return to Central Java Province; and how tourist satisfaction affected tourists' intention to return to Central Java Province (Borobudur Temple).Methodology: Data was collected from tourists who visited Indonesia's Borobudur temple as the survey's target population. In this study, surveys were conducted during a two-month period from June to August 2021 using the convenience sampling methodology. Through the use of an online survey and questionnaire, data was gathered. The SPSS for Windows 26 application was utilized for the linear regression analysis step in the data analysis process. Validity tests, reliability tests, and coefficient of determination tests were the analysis methods applied.Finding: The perception of a destination has a significant impact on visitor satisfaction, visitor perception also has a significant impact on visitor revisit intention, visitor experience also has a significant impact on visitor satisfaction, and visitor experience also has a significant impact on visitor revisit intention.Conclusion: More tourists will visit Borobudur Temple, the most beautiful temple in the world if the location has a positive and attractive image. Also, the experience of tourists has a big impact on how happy they are after seeing Borobudur Temple. If visitors to Borobudur Temple have an extraordinary experience, their satisfaction with their visit will increase. In addition, the experience of visitors has a huge impact on their plans to return; more and more people will visit Borobudur Temple if their happiness with the experience is fulfilled.